2006
DOI: 10.1029/2005jd006976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the atmospheric temperature and moisture conditions above Dome C (Antarctica) during austral summer and fall months

Abstract: [1] Two sets of radiosounding measurements were taken at Dome C (Antarctica) in December 2003 and January 2003, using RS80-A, RS80-H, and RS90 Vaisala radiosondes, and from March to May 2005, employing the RS92 model. They were examined following accurate correction procedures to remove the main relative humidity dry bias and the temperature and humidity lag errors. The results showed that a strong cooling usually characterizes the thermal conditions of the whole troposphere from December/January to April/May,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 38 publications
5
47
0
2
Order By: Relevance
“…e frequent occurrence of inversions in the Arctic and Antarctic was con rmed by Tomasi et al [13], Vihma et al [14], and Nygård et al [15,16] who showed their link with temperature inversions and the occurrence of low clouds.…”
Section: Introductionmentioning
confidence: 84%
“…e frequent occurrence of inversions in the Arctic and Antarctic was con rmed by Tomasi et al [13], Vihma et al [14], and Nygård et al [15,16] who showed their link with temperature inversions and the occurrence of low clouds.…”
Section: Introductionmentioning
confidence: 84%
“…The temperature sensor mounted in the Vaisala RS 92 sondes is an F-Thermocup (Jauhiainen et al 2005), which has been described by Luers (1997). The most important source of errors in these sensors is the solar heating (Tomasi 2006). Considering the elevation angle at Dome C, and the fact that only data gathered during the winter were considered, a correction for solar heating is not necessary.…”
Section: Instrumentation and Quality Assessment Of Temperature Profilesmentioning
confidence: 99%
“…Furthermore, whatever the season considered, it is shown that multilayer clouds occur over Antarctica. (Tomasi et al, 2006). Situated on top of a dome, there is no katabatic wind as in the case of the costal station of Dumont d'Urville (66 • S, 140 • E; 0 m a.s.l.)…”
mentioning
confidence: 99%